Continuously improving outcome over time after second allogeneic stem cell transplantation in relapsed acute myeloid leukemia: an EBMT registry analysis of 1540 patients - Schmälter, Ann-Kristin; Ngoya, Maud; Galimard, Jacques-Emmanuel; Bazarbachi, Ali; Finke, Jürgen; Kröger, Nicolaus; Bornhäuser, Martin; Stelljes, Matthias; Stölzel, Friedrich; Tischer, Johanna; Schroeder, Thomas; Dreger, Peter; et al. (Blood cancer journal, 2024)
Second allogeneic stem cell transplantation (alloSCT2) is among the most effective treatments for acute myeloid leukemia (AML) relapse after first alloSCT (alloSCT1). Long-term EBMT registry data were used to provide large scale, up-to-date outcome results and to identify factors for improved outcome. Among 1540 recipients of alloSCT2, increasing age, better disease control and performance status before alloSCT2, more use of alternative donors and higher conditioning intensity represented important trends over time. Between the first (2000-2004) and last (2015-2019) period, two-year overall and leukemia-free survival (OS/LFS) increased considerably (OS: 22.5-35%, LFS: 14.5-24.5%). Cumulative relapse incidence (RI) decreased from 64% to 50.7%, whereas graft-versus-host disease and non-relapse mortality (NRM) remained unchanged. In multivariable analysis, later period of alloSCT2 was associated with improved OS/LFS (HR = 0.47/0.53) and reduced RI (HR = 0.44). Beyond, remission duration, disease stage and patient performance score were factors for OS, LFS, RI, and NRM. Myeloablative conditioning for alloSCT2 decreased RI without increasing NRM, leading to improved OS/LFS. Haploidentical or unrelated donors and older age were associated with higher NRM and inferior OS. In summary, outcome after alloSCT2 has continuously improved over the last two decades despite increasing patient age. The identified factors provide clues for the optimized implementation of alloSCT2.
Gesehen am 29.11.2024